Multilateral teleoperation under asymmetric time delays: L2 stability and robustness. (7th June 2017) - Tumerdem, Ugur
Multilateral teleoperation is the general name given to haptic teleoperation with multiple robots and operators. It is the generalization of two robot bilateral teleoperation systems to N robots. One of the applications of multilateral teleoperation is haptic training, where multiple operators can move multiple master robots, and in consensus, they can control a single slave robot. This enables the operators to influence each other's motion with their force inputs and a more experienced operator can instruct/train a novice operator for teleoperation. In multilateral systems, existence of multiple robots and multiple communication channels between robots poses difficulties in the analysis of stability and control design. Because of the distributed nature of the problem, and especially in the presence of time delays in the communication links between robots, stability of the networked system becomes harder to guarantee. This article presents a method for checking the L 2 stability of multilateral teleoperation systems with N robots and symmetric or asymmetric time delays between them. Following this, a scalable four-channel-based distributed control law is proposed under the light of the proposed stability criterion which can guarantee delay-independent stability and enable high-performance haptic teleoperation. Furthermore, robust stability of the proposed control architecture is shown using μ analysis. Finally, theoretical results are validated with experiments that include comparisons of the proposed method with two-channel-based passive and absolutely stable systems.